Preparation and micro-wetting mechanism analysis of highly permeable-moistening additive for coal seam water injection based on plant extraction technology. (15th August 2022) - Zhang, Qingtao; Xing, Xueyang; Zhou, Gang; Hu, Yingying; Shang, Shichang; Fu, Mingming; Ma, Hui; Li, Haifeng; Men, Yanqing
Highlights: An environmental protection clean high-efficiency strong permeability and moistening material was developed. Micro wetting dynamic characteristics of the new material were proved. The dust reduction effect of the new dust suppression material is significantly better than that of the traditional surfactant. Abstract: To further reduce the concentration of dust in coal mining, improve the working environment, ensure the occupational safety and health of miners, and improve the safety construction level of intelligent mines, in this study, alginate from Enteromorpha prolifera was extracted by plant extraction technology to prepare sodium alginate. Then, the extracted sodium alginate was modified by free radical polymerization graft copolymerization theory combined with micro-wetting mechanism to develop a strong permeability and moisturizing material suitable for specific coal types, and the characteristics of the material were tested and characterized. Through molecular dynamics simulation of the highly permeable and moistening material, the wetting mechanism of the material is clarified, and the diffusion coefficient of water molecules in gas coal is 1.37×10 −4 cm 2 /s, It provides theoretical support for the technical system of mine dust prevention and control. Finally, the synthetic material is applied to the coal seam water injection process of the Qiwu coal mine so that the average dust reduction rate of total dust and exhalation dust before and after application is increased from approximately 50% when using the conventional surfactant to approximately 80% when using the strong permeability and moistening synthetic material. The effect is obviously better than that of the conventional surfactant, and the application effect is more remarkable.